2021
DOI: 10.1021/acs.macromol.0c02227
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Steric and Positioning Effects of Comonomer Substituents on α-Diimine Palladium-Catalyzed Vinyl Arene/CO Copolymerization

Abstract: To better understand the substituent effects of vinyl arene, a series of substituted styrenes with different groups and locations (n-X-St, n = 2, 3, 4; X = H, Me, t Bu, MeO, t BuO, F, Cl, and Br) were used as comonomers for palladium-catalyzed vinyl arene/CO copolymerization. Dibenzobarrelene-based α-diimine palladium catalyst Pd1 was capable of catalyzing alternating copolymerizations of substituted styrene comonomers and CO in a living fashion, which excluded the effect of the palladium catalyst. Electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…The mechanism of polyketone formation using vinyl arenes favors the coordination of electron‐rich alkenes, as opposed to electron‐poor alkenes, with palladium ions, which results in higher catalytic activities. [ 39–41 ] By comparison, polymerization reactions conducted with p ‐methoxystyrene also exhibited high catalytic activity and vinyl arene insertion (entries 3 and 6 of Table 3). Other groups have reported that the copolymerization of p ‐methoxystyrene and CO is unfavorable and that homopolymerization of p ‐methoxystyrene occurs in the presence of CO. [ 38,41 ] Based on 1 H NMR analyses of the polymers of entry 3 (Table 3), polymers synthesized from p ‐methoxystyrene and CO are estimated to be a mixture of polyketone (minor component) and homopolymers of p ‐methoxystyrene (major component).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of polyketone formation using vinyl arenes favors the coordination of electron‐rich alkenes, as opposed to electron‐poor alkenes, with palladium ions, which results in higher catalytic activities. [ 39–41 ] By comparison, polymerization reactions conducted with p ‐methoxystyrene also exhibited high catalytic activity and vinyl arene insertion (entries 3 and 6 of Table 3). Other groups have reported that the copolymerization of p ‐methoxystyrene and CO is unfavorable and that homopolymerization of p ‐methoxystyrene occurs in the presence of CO. [ 38,41 ] Based on 1 H NMR analyses of the polymers of entry 3 (Table 3), polymers synthesized from p ‐methoxystyrene and CO are estimated to be a mixture of polyketone (minor component) and homopolymers of p ‐methoxystyrene (major component).…”
Section: Resultsmentioning
confidence: 99%
“…[ 39–41 ] By comparison, polymerization reactions conducted with p ‐methoxystyrene also exhibited high catalytic activity and vinyl arene insertion (entries 3 and 6 of Table 3). Other groups have reported that the copolymerization of p ‐methoxystyrene and CO is unfavorable and that homopolymerization of p ‐methoxystyrene occurs in the presence of CO. [ 38,41 ] Based on 1 H NMR analyses of the polymers of entry 3 (Table 3), polymers synthesized from p ‐methoxystyrene and CO are estimated to be a mixture of polyketone (minor component) and homopolymers of p ‐methoxystyrene (major component). The terpolymer in entry 6 (Table 3) displays a 31% insertion of p ‐methoxystyrene‐CO units and incorporates small amounts of poly( p ‐methoxystyrene).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has preciously found that increasing the steric bulk of the α ‐diimine ligand backbone is highly efficient for enhancing stability and living fashion of α ‐diimine nickel and palladium catalysts for (co)polymerization of ethylene and polar monomer 114–122 . This approach is also applied to enhancement on palladium‐catalyzed CO/styrene copolymerization 17,18,114,115 .…”
Section: [Nn] Bidentate Palladium Catalystsmentioning
confidence: 99%
“…Gao et al synthesized bulkier dinaphthyobarrelene backbone-based α-diimine Ni (II) and Pd (II) catalysts with 3Dconstrainedspace (II in Chart 1), and the 3D-constrained space around metal center enhanced the thermal stability, living fashion, and tolerance toward polar groups in polymerizations of ethylene and polar monomers. [25][26][27][28][29][30][31][32][33] Jian et al prepared a new α-diimine nickel catalyst with a concerted double-layer steric environment (III in Chart 1), this catalyst featured highly thermally robust was ultrahighly active toward ethylene polymerization. [34] Dai et al developed a series of highly sterically demanding α-diimine Ni (II) catalysts with abundant tert-butyl substituents (IV in Chart 1) were efficient for the synthesis of PE thermoplastic elastomer at elevated temperatures (up to 90 C).…”
mentioning
confidence: 99%